2020
DOI: 10.1021/acs.cgd.0c00768
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change Initiates Dehydration in Fluconazole Monohydrate

Abstract: Experimental and computational techniques have been used in combination, to monitor the dehydration process of fluconazole monohydrate (MH), this unveiling the dehydration mechanism at the molecular level. Experimentally, dehydration was observed to start at around 55 °C and complete around 100 °C, with metastable Pbca, Z'=1 polymorph (AH-C) as the sole product of dehydration (as determined by in-situ hot stage PXRD). Conformational and structural changes were identified as key in the initiation and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…8 In the present case, the two polymorphic cocrystals had very similar structural differences, which could be attributed to conformational adjustments. [30][31][32][33] The HSMZU molecules of the HSMZU.DMF-P1 were hydrogen-bonded by weak C-H⋯X (O, N) hydrogen bonds, as well as by moderate hydrogen N-H⋯O bonds (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In the present case, the two polymorphic cocrystals had very similar structural differences, which could be attributed to conformational adjustments. [30][31][32][33] The HSMZU molecules of the HSMZU.DMF-P1 were hydrogen-bonded by weak C-H⋯X (O, N) hydrogen bonds, as well as by moderate hydrogen N-H⋯O bonds (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…3b) and indicated that they yielded a common form after the loss of the solvents. In general, desolvation processes are known to cause conformational changes of flexible hosts, 33 leading to a change in the packing from the solvated form. The difference in temperature of the desolvation of the two polymorphic solvates was 24 °C (∼0.2 kJ mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the research to date, it may be concluded that the packing of molecules/ions in crystals and the presence of hydrogen bonds have a large impact on the dehydration process of organic compounds. 36,37 The stronger the hydrogen bonds between the water molecule and the organic part, the higher the desolvation threshold temperature. In 2016, the solid-state reversible dehydration-rehydration of monosodium alendronate (NaH 4 A) one of the bisphosphonate medications against osteoporosiswas reported.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple polymorphic forms containing different conformers as well as various solvates and a monohydrate are known for fluconazole. Two recent studies by Basford et al , investigate the hydration and dehydration mechanisms of fluconazole revealing that a minor conformational change around a hydroxyl group initiates the dehydration of the monohydrate form. As with axitinib, the polymorph obtained upon the dehydration of fluconazole monohydrate has a strong conformational similarity with the monohydrate.…”
Section: Introductionmentioning
confidence: 99%